Metyrapone prevents acute glucose hypermetabolism and short-term brain damage induced by intrahippocampal administration of 4-aminopyridine in rats. (February 2018) - García-García, Luis; Fernández de la Rosa, Rubén; Delgado, Mercedes; Silván, Ágata; Bascuñana, Pablo; Bankstahl, Jens P.; Gomez, Francisca; Pozo, Miguel A.
Abstract: Intracerebral administration of the potassium channel blocker 4-aminopyridine (4-AP) triggers neuronal depolarization and intense acute seizure activity followed by neuronal damage. We have recently shown that, in the lithium-pilocarpine rat model of status epilepticus (SE), a single administration of metyrapone, an inhibitor of the 11β-hydroxylase enzyme, had protective properties of preventive nature against signs of brain damage and neuroinflammation. Herein, our aim was to investigate to which extent, pretreatment with metyrapone (150 mg/kg, i.p.) was also able to prevent eventual changes in the acute brain metabolism and short-term neuronal damage induced by intrahippocampal injection of 4-AP (7 μg/5 μl). To this end, regional brain metabolism was assessed by 2-deoxy-2-[ 18 F]fluoro-d -glucose ([ 18 F]FDG) positron emission tomography (PET) during the ictal period. Three days later, markers of neuronal death and hippocampal integrity and apoptosis (Nissl staining, NeuN and active caspase-3 immunohistochemistry), neurodegeneration (Fluoro-Jade C labeling), astrogliosis (glial fibrillary acidic protein (GFAP) immunohistochemistry) and microglia-mediated neuroinflammation ( in vitro [ 18 F]GE180 autoradiography) were evaluated. 4-AP administration acutely triggered marked brain hypermetabolism within and around the site of injection as well as short-term signs of brain damage and inflammation. Most important, metyrapone pretreatment was able to reduce ictal hypermetabolism as well as all the markers of brain damage except microglia-mediated neuroinflammation. Overall, our study corroborates the neuroprotective effects of metyrapone against multiple signs of brain damage caused by seizures triggered by 4-AP. Ultimately, our data add up to the consistent protective effect of metyrapone pretreatment reported in other models of neurological disorders of different etiology. Highlights: Intrahippocampal 4-AP triggers ictal hypermetabolism leading to brain damage. Ictal glucose hypermetabolism assessed by in vivo PET is reduced by metyrapone. Metyrapone mitigates hippocampal neurodegeneration and apoptosis. Reactive astrogliosis induced by 4-AP is ameliorated by metyrapone pretreatment. Metyrapone did not prevent microgliosis based on TSPO-[ 18 F]GE180 autoradiography.